THE STATE OF HUMORAL IMMUNITY TO MEASLES, RUBELLA AND MUMPS IN HEALTHY PEOPLE AND PATIENTS WITH MEASLES - Zherdeva, Polina E.; Toptygina, Anna P.; Nozdracheva, Anna V.; Mamaeva, Tamara A.; Novikova, Lidia I.; Smerdova, Marina A.; Iаrmolskaia, Maria S.; Dementeva, Natalia G.; Gotvyanskay, Tat'yana P.; Semenenko, Anatoliy V. (Infekt͡s︡ii͡a︡ i immunitet, 2025)
Abstract Measles, rubella and mumps are viral infections that can be prevented with highly effective vaccines. Recently, the incidence of measles and mumps has increased in many countries, involving highly immunized populations. The aim of the study was to assess measles, rubella and mumps humoral immunity in healthy people of different ages and compare these data with measles incidence in same area during the same time period. The serum samples from 713 conditionally healthy residents of different ages from Moscow and the Moscow region with an unknown vaccination history and from 700 patients with measles collected on the 4th-5th day after onset of rash were examined. Humoral immunity was determined by ELISA using the kits from AO Vector-Best, Russian Federation and Euroimmun, Germany. It was found that in the group of 1–5-year-old subjects, the seropositivity rate was below 60%. Seroprevalence in groups over 6-year-old subjects against rubella fluctuates at the level of 87-94%, mumps - 72-83%. The most unstable situation was observed in humoral immunity against measles virus. In the group of 6-13-year-old subjects, seroprevalence increased to 79% followed by decline to 49.5% in group of 18-30-year-old subjects. The subsequent increase in seropositivity to 88.12% in the group over 51-year-old subjects was significantly lower than the calculated population immunity level (95%). Among measles patients in 2024, children and adolescents accounted for 54.32%. Comparison of measles incidence with the measles seronegative level in the same age groups revealed a clear pattern: the more seronegative were subjects, the higher measles incidence was in this group. In a similar study on measles incidence in 2013, all children and adolescents responded to the infection with a primary immune response, and among adult patients, a secondary immune response was detected in 12-18%. In 2024, among children and adolescents with measles, 9-12% responded with a secondary immune response, and in adult groups, the proportion of secondary response reached 44%, indicating that individuals vaccinated in childhood but who lost measles antibodies during life actively contribute to measles cases. Vaccination of seronegative grades 10-11 adolescents is necessary.